Collaborative Governance in the Management of Village Owned Enterprises Ponggok Sub District Polanharjo District Klaten Central Java 2016 - Kohen Sofi; Dyah Mutiarin (Journal of Government and Civil Society, 2018)
The Law No. 6 of 2014 article 1 mention about the village-owned enterprises as the business entity which the capital is owned by the village in order to be managed for community welfare. The government of village should be able to see the potential of the village to be managed along with the community and private sector to maintain its sustainability. The successful of Ponggok village to establish and run the village-owned enterprises Tirta Mandiri brings the Ponggok village as one of the richest village in Indonesia with the 9.6 billion rupiah income per year. This research aims to see how the ability of the collaborative governance to push accountability and transparency factors in managing the village-owned enterprises in 2016. This research used the method of collaborative governance through the data collection and interview towards the related actors. According to the data, the collaborative governance in the management of Ponggok village-owned enterprises involved three actors such as the government of the village, community and private sector. Collaborative governance be able to push the accountability and transparency in the management of village-owned enterprises by those collaborative actors. The result of collaborative governance can be felt by the villagers in form of welfare.